Speaker Recognition System for Home Security using Raspberry Pi and Python - Bageshree Pathak, Dr; Kulkarni, Shriyanti (International Journal of Engineering and Technology, 2018)
The transfer of manual controls to machine controls is automation. Automation is the need of the hour. Home automation is automation of home systems to create smart homes. It includes security systems, appliance control and environment control. The increasing need for safety and security has brought biometric security systems to the forefront. Speech being unique and individualistic can be used for biometric identification. The proposed system is a prototype which can be fitted for speaker recognition for home security. The system will identify the registered speakers and will allow access to the recognized speaker. The system is implemented on Raspberry pi platform using Python language.Â Â